Lifestyle Medicine in a Concierge Practice: My Journey - Serna, Dorothy Cohen (Am J Lifestyle Med, 2019)
While lifestyle medicine (LM) has been increasingly recognized for its value in preventing and managing chronic disease, the conventional primary care practice has struggled to be a financially viable model for this time-intensive, highly personalized approach. However, the concierge medicine model provides many advantages to those seeking to incorporate the tenets of LM. Concierge medicine is characterized by smaller patient panels, extended visits, continuous follow-up, and a distinctive emphasis on prevention and wellness. These characteristics promote high-quality, individualized care. North Cypress Internal Medicine and Wellness was able to successfully transform from a more traditional medical model to one with essential LM-focused offerings with expert assistance, as well as ongoing support from a dedicated team of lifestyle-oriented health professionals who provide wellness coaching, proactive chronic care management, and prevention programs. This article describes the transition and includes specific details of services and care offered at a concierge practice. It illustrates how this alternative model can provide an effective solution for delivering the full potential of LM.